The inside scoop: Acceptance and rejection at the Journal of International Economics - Ivan Cherkashin; Susumu Imai; Kala Krishna; Demidova Svetlana (Queen's University, Department of Economics, 2008)
There is little work on the inner workings of journals. What factors seem to affect the ability to publish in a journal? Could simple rules (which are already used by some journals) like the immediate rejection of a significant minority of papers, help to streamline the process? At what cost? How well do journals seem to do in choosing papers? What can we say about the extent of type 1 and type 2 errors? Do editors seem to have uniform standards or are some harsher than others? We use data on submissions to the Journal of International Economics to help answer these questions.
Keywords: F0; 330; Publishing in Economics; Performance Evaluation; Probit Model; Selection Bias; Fachzeitschrift; Wirtschaftswissenschaft; Bibliometrie; Bewertung; USA